2020
DOI: 10.1186/s40478-020-01010-8
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell mass cytometry reveals complex myeloid cell composition in active lesions of progressive multiple sclerosis

Abstract: Myeloid cells contribute to inflammation and demyelination in the early stages of multiple sclerosis (MS), but it is still unclear to what extent these cells are involved in active lesion formation in progressive MS (PMS). Here, we have harnessed the power of single-cell mass cytometry (CyTOF) to compare myeloid cell phenotypes in active lesions of PMS donors with those in normal-appearing white matter from the same donors and control white matter from non-MS donors. CyTOF measurements of a total of 74 targete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 67 publications
(134 reference statements)
0
34
0
Order By: Relevance
“…In biopsies of active lesions in early cases of MS, diseasesassociated microglia subsets showed the expected general downregulation of GPCR genes associated with microglia homeostasis. Single-cell mass cytometry indeed confirmed the appearance of active MS lesion-enriched clusters with a downregulated surface expression of P2Y 12 , CX3CR1, and GPR56 (31).…”
Section: Discussionmentioning
confidence: 69%
“…In biopsies of active lesions in early cases of MS, diseasesassociated microglia subsets showed the expected general downregulation of GPCR genes associated with microglia homeostasis. Single-cell mass cytometry indeed confirmed the appearance of active MS lesion-enriched clusters with a downregulated surface expression of P2Y 12 , CX3CR1, and GPR56 (31).…”
Section: Discussionmentioning
confidence: 69%
“…Using single-cell mass cytometry analysis, the phenotype of activated microglia in patients with progressive MS was determined. The study revealed that highly phagocytic and activated microglia downregulated the expression of homeostatic markers such as P2Y12 and GPR56 and upregulated the expression of proteins involved in phagocytic activity and microglial activation including CD68, CCR2, CD64, CD32, CD95, and CCL4 [ 38 ]. Besides the physical presence of microglia at sites of demyelination and an upregulation of various markers, the pathophysiological function of microglia in progression is largely unclear.…”
Section: Mechanism Of Disease Progression In Msmentioning
confidence: 99%
“…Within the CNS parenchyma, resident and invading macrophages play complex roles both preclinically and in established lesions ( 71 ). Monocyte invasion might, however, vary at different disease stages, with less MdM infiltrates observed in progressive MS compared to RRMS ( 200 ).…”
Section: Myeloid Dwellers and Trespassers At Cns Interfaces Upon Automentioning
confidence: 99%